2013
DOI: 10.1016/j.immuni.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the Transcription Factor Foxp3 by the Deubiquitinase USP7 Increases Treg-Cell-Suppressive Capacity

Abstract: SUMMARY Stable Foxp3 expression is required for the development of functional regulatory T (Treg) cells. Here, we demonstrate that the expression of the transcription factor Foxp3 can be regulated through the polyubiquitination of multiple lysine residues, resulting in proteasome-mediated degradation. Expression of the deubiquitinase (DUB) USP7 was found to be upregulated and active in Treg cells, being associated with Foxp3 in the nucleus. Ectopic expression of USP7 decreased Foxp3 polyubiquitination and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
249
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(264 citation statements)
references
References 49 publications
14
249
1
Order By: Relevance
“…74 Subsequently, FOXP3 was also found to undergo ubiquitination and the that ubiquitination would lead to its degradation. 31,55 Since both ubiquitination and acetylation are restricted to lysine residues, acetylation may compete with poly-ubiquitination to stabilize FOXP3. 57 Two acetyltransferases, Tip60 and p300, have been reported as enzymes that are responsible for FOXP3 acetylation.…”
Section: Mechanisms Underlying the Suppressive Function Of Foxp3 1 Trmentioning
confidence: 99%
See 2 more Smart Citations
“…74 Subsequently, FOXP3 was also found to undergo ubiquitination and the that ubiquitination would lead to its degradation. 31,55 Since both ubiquitination and acetylation are restricted to lysine residues, acetylation may compete with poly-ubiquitination to stabilize FOXP3. 57 Two acetyltransferases, Tip60 and p300, have been reported as enzymes that are responsible for FOXP3 acetylation.…”
Section: Mechanisms Underlying the Suppressive Function Of Foxp3 1 Trmentioning
confidence: 99%
“…Further, adoptive transfer of USP7 knockdown or USP7 inhibitor-treated Treg cells have reduced function in resolving induced colitis in mice. 55 Phosphorylation is the most common studied post-translational modification of proteins. 79 It has been reported that phosphorylation at Ser418 in the C-terminal DNA binding domain of FOXP3 positively regulates its DNA binding activity and transcriptional regulation that affects Treg cell suppressive function.…”
Section: Mechanisms Underlying the Suppressive Function Of Foxp3 1 Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, low-dose cadmium has growth-promoting effects on NPrEC cells and induces transient overexpression of genes with oncogenic and immunomodulation functions, including TNF and Il13ra2 [17]. Ubiquitin specific peptidase 7 (USP7), also known as herpes virus-associated ubiquitin-specific protease (HAUSP), is hydrolase that deubiquitinates target proteins such as FOXO4, p53/TP53, MDM2, PTEN, PPARG, and other and thus participate in control of cell growth repression and apoptosis [18][19][20]. There is data that early adipogenesis is regu lated through USP7-mediated deubiquitination of the histone acetyltransferase TIP60 [21].…”
Section: We Have Studied the Effect Of Chromium Disilicide And Titanimentioning
confidence: 99%
“…[3][4][5] On the other hand, the Foxp3 protein is regulated at the posttranslational level by acetylation, phosphorylation, and ubiquitination, which detemine its DNA binding, protein stability, and degradation under inflammation. [6][7][8][9][10] Understanding functional plasticity and stability could provide new insights in promoting Treg-based clinical therapies for autoimmune disease, organ transplantation, and cancer. 11 In this issue, we have assembled a series of up-to-date reviews on the functional plasticity of Tregs to address and discuss how Tregs may sense the initiation and progression of inflammation in different physiological microenvironments.…”
mentioning
confidence: 99%